Epigenetic upregulation of endogenous VEGF-A reduces myocardial infarct size in mice. - Mikko P Turunen (Public Library of Science (PLoS), 2014)
"Epigenetherapy" alters epigenetic status of the targeted chromatin and modifies expression of the endogenous therapeutic gene. In this study we used lentiviral in vivo delivery of small hairpin RNA (shRNA) into hearts in a murine infarction model. shRNA complementary to the promoter of vascular endothelial growth factor (VEGF-A) was able to upregulate endogenous VEGF-A expression. Histological and multiphoton microscope analysis confirmed the therapeutic effect in the transduced hearts. Magnetic resonance imaging (MRI) showed in vivo that the infarct size was significantly reduced in the treatment group 14 days after the epigenetherapy. Importantly, we show that promoter-targeted shRNA upregulates all isoforms of endogenous VEGF-A and that an intact hairpin structure is required for the shRNA activity. In conclusion, regulation of gene expression at the promoter level is a promising new treatment strategy for myocardial infarction and also potentially useful for the upregulation of other endogenous genes.